Two Groups of eGFP-Expressing Neurons with Distinct Characteristics in the Neocortex of GIN Mice. (15th April 2019) - Wang, Chunlian; Yu, Baocong; Li, Meiyi; Zhao, Chunjie; Roper, Steven N.; Chen, Huanxin
Abstract: GIN (GFP-expressing inhibitory interneuron) transgenic mice are believed to express the enhanced GFP (eGFP) in a subset of somatostatin (SST)-expressing interneurons in the neocortex and have been widely used in the study on SST interneurons. Previous studies showed that eGFP + neurons in the neocortex are distributed in the layer II-IV and upper layer V (cortical eGFP neurons) and contain SST. In this study, we reported a new group of eGFP + neurons in GIN mice at early postnatal ages, which was located in the deep layer of the lateral neocortex as clusters (cluster eGFP neurons). Cluster eGFP neurons were noticeable at birth but disappeared within two months, in contrast to cortical eGFP neurons that started to appear around postnatal day 3 to 5 and existed through life. Cluster eGFP neurons were not immunoreactive for SST antibodies, contrary to cortical eGFP neurons. They were also not immunolabeled by parvalbumin, a marker for another major type of interneurons, and Ca 2+ /calmodulin-dependent kinases II, a commonly used marker for excitatory neurons. Firing rate, afterhyperpolarization, and excitatory synaptic activity significantly enhanced in cortical eGFP neurons during postnatal development, but these properties remained mostly unchanged in cluster eGFP neurons. Short-term plasticity of the excitatory synapse showed robust facilitation in cortical eGFP neurons but depression in cluster eGFP neurons. These results implied that eGFP might also be expressed in other types of cortical neurons in addition to SST-containing interneurons in GIN mice at early postnatal ages. Highlights: A new group of eGFP + neurons, in addition to the previously reported one, is present in the neocortex of GIN mice. Those eGFP + neurons are distributed in the deep cortical layers as clusters and disappear mostly after the second postnatal month. They are not immunoreactive for SST, PV, GAD, and CaMKII antibodies. They display distinct intrinsic and synaptic properties and postnatal development.